Krøyer and Paris : French connections and Nordic colours - Krøyer, Peder Severin, 1851-1909 (Skagens Kunstmuseer ; Aarhus University Press ; Muše Marmottan Monet, 2022)
A lover of light?: in 1912, a French critic used these words to describe the great Danish painter Peder Severin Krøyer, who had close ties to the French art scene for more than two decades. Krøyer first visited Paris in 1877, and his many letters clearly show the impact French art had on Krøyer?s own development as a painter, on the artists' colony in Skagen, and on Danish art history in general. In 'Krøyer and Paris. French Connections and Nordic Colours', art historians Mette Harbo Lehmann and Dominique Lobstein describe Krøyer's artistic development from the Golden Age tradition favoured by the Danish academy to Naturalism and the Modern Breakthrough. They show how inspiration from France can be traced in his painting technique and his open-air paintings from Skagen, revealing how French Naturalism made its mark on Krøyer's distinctive style. Exhibition: Skagens Museum, Denmark (13.05.-18.09.2022).